Gender-specific outcomes in immune checkpoint inhibitor therapy for advanced or metastatic urothelial cancer: a systematic review and meta-analysis - Schneidewind, Laila; Kiss, Bernhard; Zengerling, Friedemann; Borkowetz, Angelika; Graf, Sebastian; Kranz, Jennifer; Dräger, Desiree L.; Graser, Annabel; Bellut, Laura; Uhlig, Annemarie (Journal of Cancer Research and Clinical Oncology, 2023)
Purpose: To analyze gender-specific differences in survival parameters in advanced or metastatic urothelial cancer patients undergoing immune checkpoint inhibition. Methods: The primary aim of this systematic review and meta-analysis was to evaluate gender-specific differences in disease-free (DFS), progression-free (PFS), cancer-specific survival (CSS), event-free survival (EFS), overall survival (OS) and objective response rate (ORR). The sources MEDLINE, Embase and Cochrane Library were systematically searched from January 2010 to June 2022. No restrictions were made concerning language, study region or publication type. A comparison of gender-specific differences in survival parameters was performed using a random-effects meta-analysis. A risk of bias assessment was done using the ROBINS-I tool. Results: Five studies were included. In a random-effect meta-analysis of the studies, PCD4989g and IMvigor 211 with both using atezolizumab, females were more likely to have better objective response rate (ORR) than men (OR 2.24; 95% CI 1.20–4.16; p = 0.0110). In addition, females had a comparable median OS to men (MD 1.16; 95% CI − 3.15–5.46; p = 0.598). In summary, comparing all results, a tendency was seen toward better response rates and survival parameters in female patients. The risk of bias assessment yielded an overall low risk of bias. Conclusions: There is a tendency toward better outcomes in women for immunotherapy in advanced or metastatic urothelial cancer, but only for the antibody atezolizumab women have a significantly better ORR. Unfortunately, many studies fail to report gender-specific outcomes. Therefore, further research is essential when aiming for individualized medicine. This research should address immunological confounders.
CRIS-Team Scopus Importer:2023-05-19
Keywords: Bladder cancer; Gender; Immunotherapy; Overall survival; Urothelial cancer